An effective method for delayed migration of dripping agent from linear low‐density polyethylene films. (20th December 2020) - Yang, Siqi; Zhu, Dantong; Yang, Fanghong; Li, Wenfei; Yao, Zhanhai; Liu, Bingwei
Abstract : Dripping agents are incorporated into polyethylene films to improve the hydrophility of the film surface and minimize the effects of fogging. A reactive‐type of dripping agent, 18, alkyl diethanolamine acrylic monoester (EDM), was synthesized and then grafted onto layered double hydroxides (LDHs) to delay its migration, which is due to the large size of LDHs. Then, the LDH‐ g ‐EDM compound was added to linear low‐density polyethylene (LLDPE), and dripping films were prepared for studying their properties. Mechanical properties, light transmission properties, elongational rheology properties, and thermal properties of LLDPE/EDM and LLDPE/LDHs‐ g ‐EDM films were determined. The contact angle of LLDPE/EDM film could reach 31.4° when the content of EDM was 2.0 wt%. Accelerated dripping experiments showed that the duration of dripping of the LLDPE/LDH‐ g ‐EDM film at 60 °C was prolonged to 18 days when the content of LDH was 0.6 wt% of the LLDPE matrix. This indicates that grafting EDM onto LDHs could delay its outward migration in LLDPE films.